2017
DOI: 10.4103/1119-3077.196063
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and intraoperative continuous use of dexmedetomidine on hyperalgesia after patients' remifentanil anesthesia

Abstract: In clinical surgery, after use of remifentanil anesthesia on patients, use of dexmedetomidine for anesthesia recovery can minimize adverse effects of drugs on patients and thus is worthy to be effectively promoted in clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“… 24 Furthermore, it has been demonstrated that Dex can reduce the hyperalgesia caused by remifentanil and pain stimulation, and can yield global haemodynamic stability and prevent violent injury to the throat and vocal cord. 25–27 Notably, previous reports have confirmed the efficacy of intranasal Dex as a sedative premedication to induce a favourable perioperative anxiolysis 28 and reduce emergence agitation during recovery from general anesthesia. 29 In addition, Rani et al 30 found that a single dose of Dex, administered intravenously 15 min prior to extubation, could suppress the airway reflex during recovery from general anaesthesia.…”
Section: Discussionmentioning
confidence: 92%
“… 24 Furthermore, it has been demonstrated that Dex can reduce the hyperalgesia caused by remifentanil and pain stimulation, and can yield global haemodynamic stability and prevent violent injury to the throat and vocal cord. 25–27 Notably, previous reports have confirmed the efficacy of intranasal Dex as a sedative premedication to induce a favourable perioperative anxiolysis 28 and reduce emergence agitation during recovery from general anesthesia. 29 In addition, Rani et al 30 found that a single dose of Dex, administered intravenously 15 min prior to extubation, could suppress the airway reflex during recovery from general anaesthesia.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, it is necessary to pay attention to the preoperative nursing of children with congenital heart disease, improve their negative emotions through relevant intervention measures, and improve the ISSN 2618-1584 Vol. Dexmedetomidine, a novel selective α2 adrenergic receptor agonist, has sedative, analgesic and anxiolytic effects without causing any respiratory complications [5,6] . Intranasal administration of dexmedetomidine is painless and stimulative, with high compliance of children, and can be used for preoperative administration in children [7] .…”
Section: Introductionmentioning
confidence: 99%
“…DOH monitors are usually used in clinical practice to guide the administration of anesthetics (2,3). However, there is no professional person to guide the infusion of remifentanil (analgesia) (4,5). The variability of DOH measures is related to the insufficient analgesic effect, and the feasibility of closed-loop control of propofol and remifentanil infusion using DOH feedback has been demonstrated (6,7).…”
Section: Introductionmentioning
confidence: 99%